Why don't auditors use computer-assisted audit techniques? study at small public accounting firms - Depi Lestari; Sepky Mardian; M. Asmeldi Firman (STIE Perbanas Surabaya, 2020)
This study aims to examine the effect of technology, organization, and environment on the use of Computer-Assisted Audit Techniques (CAATs). The object of this study is the auditors working at Public Accounting Firms in Jakarta area. Sampling is done using purposive sampling technique. Data collection is carried out through questionnaires. The research method used is associative research with Partial Least Square (PLS), Structural Equation Modeling (SEM), and Parallel Least Square (PLS) approaches. The results of this study show that technology, organization, and environment (TOE) do not have a significant effect on the use of CAATs. The easy and fast access to technology systems (CAATs) has not been supported by good auditor resources. The ability and skills of users are still inadequate and there are no auditors who have certification related to the use of CAATs. The audit process does not require so many complex technological roles, but simple technology that can cover the entire audit process. Most auditors use Microsoft Excel / Word in the audit process. In this case, the auditors at least have already used audit software. Small or large clients do not matter what type of CAATs the auditor uses.